Collective intelligence for translational medicine: Crowdsourcing insights and innovation from an interdisciplinary biomedical research community. (3rd October 2015) - Jane Budge, Eleanor; Maria Tsoti, Sandra; James Howgate, Daniel; Sivakumar, Shivan; Jalali, Morteza
Abstract: Translational medicine bridges the gap between discoveries in biomedical science and their safe and effective clinical application. Despite the gross opportunity afforded by modern research for unparalleled advances in this field, the process of translation remains protracted. Efforts to expedite science translation have included the facilitation of interdisciplinary collaboration within both academic and clinical environments in order to generate integrated working platforms fuelling the sharing of knowledge, expertise, and tools to align biomedical research with clinical need. However, barriers to scientific translation remain, and further progress is urgently required. Collective intelligence and crowdsourcing applications offer the potential for global online networks, allowing connection and collaboration between a wide variety of fields. This would drive the alignment of biomedical science with biotechnology, clinical need, and patient experience, in order to deliver evidence-based innovation which can revolutionize medical care worldwide. Here we discuss the critical steps towards implementing collective intelligence in translational medicine using the experience of those in other fields of science and public health. Key Messages: The scientific translation of biomedical research into clinical applications is protracted, despite the mass opportunity afforded by modern science. Barriers to translational medicine exist as a result of the impracticalities of research, organizational hurdles, and lack of an interdisciplinary workforce. Collective intelligence and crowdsourcing offer the potential to expedite the translational process by providing a platform upon which interdisciplinary workforces can communicate and collaborate, aligning biomedical research with clinical need revolutionizing health care worldwide.